Mark Manders. ([S.l.] : [s.n.], 1999)
The concept of this newspaper is based on the fascination for the fact that something outside your body, for example five calculators on a row, can make your brains think 'five'. The paper contains only fives and has been spreaded over the city of Hann. Münden in Germany, together with a regional NEWspaper.
i.s.m. SMAK Gent
Duits
boek
Keywords: Manders, Mark